Single-cell RNA sequencing uncovers heterogenous immune cell responses upon exposure to food additive (E171) titanium dioxide - Haribalan Perumalsamy; Xiao Xiao; Hyoung-Yun Han; Jung-Hwa Oh; Seokjoo Yoon; Min Beom Heo; Tae Geol Lee; Hyun-Yi Kim; Tae-Hyun Yoon (Journal of Nanobiotechnology, 2024)
Abstract The prospective use of food additive titanium dioxide (E171 TiO2) in a variety of fields (food, pharmaceutics, and cosmetics) prompts proper cellular cytotoxicity and transcriptomic assessment. Interestingly, smaller-sized E171 TiO2 can translocate in bloodstream and induce a diverse immunological response by activating the immune system, which can be either pro-inflammatory or immune-suppressive. Nevertheless, their cellular or immunologic responses in a heterogeneous population of the immune system following exposure of food additive E171 TiO2 is yet to be elucidated. For this purpose, we have used male Sprague-Dawley rats to deliver E171 TiO2 (5 mg/kg bw per day) via non-invasive intratracheal instillation for 13 weeks. After the 4 weeks recovery period, 3 mL of blood samples from both treated and untreated groups were collected for scRNAseq analysis. Firstly, granulocyte G1 activated innate immune response through the upregulation of genes involved in pro-inflammatory cytokine mediated cytotoxicity. Whereas NK cells resulted in heterogeneity role depending on the subsets where NK1 significantly inhibited cytotoxicity, whereas NK2 and NK3 subsets activated pro-B cell population & inhibited T cell mediated cytotoxicity respectively. While NKT_1 activated innate inflammatory responses which was confirmed by cytotoxic CD8+ T killer cell suppression. Similarly, NKT_2 cells promote inflammatory response by releasing lytic granules and MHC-I complex inhibition to arrest cytotoxic T killer cell responses. Conversely, NKT_3 suppressed inflammatory response by release of anti-inflammatory cytokines suggesting the functional heterogeneity of NKT subset. The formation of MHC-I or MHC-II complexes with T-cell subsets resulted in neither B and T cell dysfunction nor cytotoxic T killer cell inhibition suppressing adaptive immune response. Overall, our research offers an innovative high-dimensional approach to reveal immunological and transcriptomic responses of each cell types at the single cell level in a complex heterogeneous cellular environment by reassuring a precise assessment of immunological response of E171 TiO2. Graphical Abstract